2015
DOI: 10.4161/21505594.2014.989795
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Scrapie Infectivity: Interaction between Recombinant PrP and Scrapie Brain-Derived RNA

Abstract: The key molecular event in human cerebral proteinopathies, which include Alzheimer's, Parkinson's and Huntington's diseases, is the structural conversion of a specific host protein into a β-sheet-rich conformer. With regards to this common mechanism, it appears difficult to explain the outstanding infectious properties attributed to PrP(Sc), the hallmark of another intriguing family of cerebral proteinopathies known as transmissible spongiform encephalopathies (TSE) or prion diseases. The infectious PrP(Sc) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 49 publications
(72 reference statements)
2
23
1
Order By: Relevance
“…The minimal size of the nucleic acid molecule that can convert PrP into PrP Sc -like species is also arguable (18,36,45). The particular structure of the nucleic acid also seems to be important for the binding affinity and specificity.…”
Section: Prp Requires Polyanions Such As Rna or Dna As Partners Durmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimal size of the nucleic acid molecule that can convert PrP into PrP Sc -like species is also arguable (18,36,45). The particular structure of the nucleic acid also seems to be important for the binding affinity and specificity.…”
Section: Prp Requires Polyanions Such As Rna or Dna As Partners Durmentioning
confidence: 99%
“…Although no single RNA or DNA molecule has been found to be associated with PrP infectivity in vivo, recent work provides strong evidence that small RNA sequences (27-and 55-mers) associated with brain scrapie material can trigger the conversion of the recombinant protein to a disease-causing form when incubated with recombinant PrP C (45). Although not all preparations induced prion-like disease in recipient mice, these results indicate that a sustained RNA population is present in scrapie-associated fibrils, in partial disagreement with the protein-only hypothesis (27).…”
Section: Prp Requires Polyanions Such As Rna or Dna As Partners Durmentioning
confidence: 99%
“…While restoration of TSE agent infectivity has been tried for many years in various preparations, 39,55 a small amount of infectivity was recently restored by combining phenol purified 263K brain nucleic acids with recombinant PrP. 13 Non-PrP proteins that are particle-associated 20,46 may also be needed to effectively transmit an agent genome from among the many nucleic acids present in all highly infectious preparations. 41,45 Thiourea (ThU) alone, or combined with urea, is very effective for destroying >4 logs of TSE infectivity within 1 hr at 22 C, and ThU has not been used previously for TSE agent disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Misfolded recombinant PrP is not reproducibly infectious in animal or culture assays, even though massive amounts of PrPres amyloid are readily generated in a test tube. 4,[10][11][12][13] Huge increases in PrP-res can also coincide with a >5 log loss of FU-CJD agent from chronically infected living cell cultures. 12 This PrP-res is indistinguishable from the "infectious" PrP-res form, yet it is unable to produce any detectable agent in sensitive infectivity culture assays.…”
Section: Introductionmentioning
confidence: 99%
“…While particular mechanisms of these conformational and biological changes have been unknown, it has been demonstrated that they require additional chaperone molecules such as lipids, proteoglycans and RNAs (Mabbott, 2017). TSE progressing is related to the exponential growth of PrP C transformation into its abnormal isoform PrP Sc (Saba et al, 2012), which is characterized by the changed tertiary structure of the molecule, where the α-spirals have transformed to make a new conformation with the β-layers (Simoneau et al, 2015). The characteristic histopathologic CNS changes in TSE include brain vacuolation, neurodegeneration, microgliosis, astrocytosis and pathological accumulation of PrP Sc (Mabbott, 2017).…”
Section: молекулярная и клеточная биологияmentioning
confidence: 99%